Iron Reduces M1 Macrophage Polarization in RAW264.7 Macrophages Associated with Inhibition of STAT1 - Zhen-Shun Gan; Qian-Qian Wang; Jia-Hui Li; Xu-Liang Wang; Yi-Zhen Wang; Hua-Hua Du (Mediators of Inflammation, 2017)
Iron metabolism in inflammation has been mostly characterized in macrophages exposed to pathogens or inflammatory conditions. The aim of this study is to investigate the cross-regulatory interactions between M1 macrophage polarization and iron metabolism. Firstly, we characterized the transcription of genes related to iron homeostasis in M1 RAW264.7 macrophages stimulated by IFN-γ. The molecular signature of M1 macrophages showed high levels of iron storage (ferritin), a low level of iron export (ferroportin), and changes of iron regulators (hepcidin and transferrin receptors), which favour iron sequestration in the reticuloendothelial system and are benefit for inflammatory disorders. Then, we evaluated the effect of iron on M1 macrophage polarization. Iron significantly reduced mRNA levels of IL-6, IL-1β, TNF-α, and iNOS produced by IFN-γ-polarized M1 macrophages. Immunofluorescence analysis showed that iron also reduced iNOS production. However, iron did not compromise but enhanced the ability of M1-polarized macrophages to phagocytose FITC-dextran. Moreover, we demonstrated that STAT1 inhibition was required for reduction of iNOS and M1-related cytokines production by the present of iron. Together, these findings indicated that iron decreased polarization of M1 macrophages and inhibited the production of the proinflammatory cytokines. The results expanded our knowledge about the role of iron in macrophage polarization.